Psychological Precursors and Manifestations of Daily Beyond-Duties Engagement Within the Assistance and Creative Professions - Bożek, Agnieszka (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2021)
The study’s first goal was to explore and analyze ‘beyond-duties engagement’ (employee engagement that exceeds basic professional duties) within the assistance and creative professions. The second goal was to explore relationships of daily beyond-duties engagement with autonomy in action, feedback from others, positive affect and subjective assessment of one’s competences. Each participant completed a daily diary for 5-6 days, and data were obtained from 64 employees, aged 21-61 (M = 38.91, SD = 8.99), from each profession. Qualitative sorting of beyond-duties engagement yielded twelve categories with forty subcategories. Hierarchical linear modelling demonstrated a positive relationship between feedback from others and subjective assessment of one’s competences with enhanced beyond-duties engagement. A mediation role of positive affect was also observed. When considered within the relevant organizational context, these findings may help predict how an employee, from a given profession, is likely to respond to specific, positive stimuli at work.